Vocabulary Teaching Strategies By Efl Teachers Of Junior High School Level - Esra Elisabeth panjaitan; Exsanti Jumina Sibarani; Erikson Saragih (Institut Agama Islam Negeri Palopo, 2021)
Abstract. This research is dedicated to the research vocabulary teaching strategies by EFL teachers of Junior High School. The rationale of this research is to investigate the teachers’ strategies in the teaching and learning process. In addition, this study applied a qualitative approach to analyze data Data were collected in-depth survey by questionnaire with ten teachers as respondents. In collecting data there 3 steps, namely The writer selected the respondents (ten teachers), the writer made ten questions in a questionnaire for respondents by using google form and The writer wrote a survey’s answer based on the survey that had been recorded.In this research, the questions are divided into two parts namely, multiple-choice and essay. In the multiple-choice, the teacher just chose one of the options and on the essays, the teacher can give short or long answers. The data were analyzed in some way:(1)classify data,(2)make a transcript data in written language, (3)Give a sign, and (4) gather the same sign. In general, a result shows the teacher strategies in (1) teacher preparation in teaching vocabulary,(2) sources of vocabulary teaching, (3) kind of teacher question, (4) teacher activities during the teaching process, and (5) students activities during the earning process. This result can be seen by the teacher’s answers in the questionnaire. This result is expected to help the teacher to learn vocabulary and will greatly contribute for the teacher to teaching vocabulary.